Contestação, comunicação e consumo: a cena straight edge brasileira - Tangerino, Denise de Paiva Costa (2011)
The present thesis focuses on the analysis of communicational actions articulated to consumerist practices of one of the most lasting contemporary juvenile movements, the socalled straight edge. Is proposal includes both the criticism towards mass media and capitalist-rooted consumer society , spreading idiosyncratic values. Assuming a antisystemic approach, it also builds own paths of consumerism, both symbolic and material. It is also to be noted, yet, a strong communicational and technological basis of this movement, which complexly articulates local, regional and global flows. Through a multi-methodological emphasis documental research, bibliographic revision, observation with ethnographic approach the thesis aims to spot within the speeches and narratives of the youngsters the acting line and movement impacts in terms of tendencies and/or new approaches towards the upraising interaction among mediatic cultures and consumerist cultures.